Periodontal disease and incident prediabetes and diabetes: The Hispanic Community Health Study/Study of Latinos. (23rd February 2022) - Laniado, Nadia; Khambaty, Tasneem; Hua, Simin; Kaplan, Robert; Llabre, Maria M.; Schneiderman, Neil; Singer, Richard H.; Qi, Qibin; Cai, Jianwen; Finlayson, Tracy L.; Whalen, Adam M.; Isasi, Carmen R.
Abstract: Aim: To examine whether baseline periodontal disease is independently associated with incident prediabetes and incident diabetes in Hispanics/Latinos in the United States. Materials and Methods: This study examined 7827 individuals, 18–74 years of age without diabetes, from the Hispanic Community Health Study/Study of Latinos. Participants received a full‐mouth periodontal examination at baseline (2008–2011), and the disease was classified using the Centers for Disease Control and Prevention/American Academy of Periodontology case definitions. At Visit 2 (2014–2017), incident prediabetes and diabetes were assessed using multiple standard procedures including blood tests. Multivariable survey Poisson regressions estimated the rate ratio (RR) and 95% confidence intervals (CIs) of incident prediabetes and incident diabetes associated with periodontal disease severity. Results: Among the individuals without prediabetes or diabetes at baseline, 38.8% ( n = 1553) had developed prediabetes and 2.2% ( n = 87) had developed diabetes after 6 years. Nineteen percent ( n = 727) of individuals with prediabetes at baseline developed diabetes after 6 years. Adjusting for all potential confounders, no significant association was found between periodontal disease severity and either incident prediabetes (RR: 0.93; 95% CI: 0.82–1.06) or incident diabetes (RR: 0.99; 95% CI: 0.80–1.22). Conclusions: Our findings suggest that among a diverse cohort of Hispanic/Latino individuals living in the United States, there was no association between periodontal disease severity and the development of either prediabetes or diabetes during a 6‐year follow‐up period.